Pengembangan media pembelajaran audio visual berbasis video dokumenter pada materi kultur jaringan tanaman anggrek hitam (Coelogyne Pandurata) di SMKN 1 Lubuk Dalam - mellisa; Ana Rofiana (Biology and Education Journal, 2022)
Development of audio visual learning media based on documentary video on tissue culture material of black orchid (coelogyne pandurata) at SMKN 1 Lubuk Dalam. This research was conducted on August 20, 2020. This development research uses the ADDIE development model with several stages, namely Analysis, Design and Development. The data collection instruments used were in the form of validation sheets and student response questionnaires. The sampling technique used in this research is simple random sampling. Collecting data using validation sheets and student response questionnaires. The data were analyzed using a scale method analysis technique with a modified Likert scale. The results of this study are in the form of products, namely audio-visual learning media based on documentary videos. The data of this study were obtained from the results of validation by material experts, media experts, learning experts and limited trials of class XII PPT SMK N 1 Lubuk Dalam students who had studied tissue culture material. The results of validation by material experts show that the audio-visual learning media based on documentary video that was developed got an average percentage of 91.67% (very valid), from media experts 93.75% (very valid), learning experts at 100% ( very valid). So that the overall average result of the assessment of audio-visual learning media based on documentary videos by experts is 95.14% with a very valid category. The audio-visual learning media based on the tissue culture documentary video that was developed received a very good response from students. This can be seen from the average student response of 90.74% (very good). Based on the results of the validation of the experts and the results of the student response questionnaire, the product was obtained in the form of audio-visual learning media based on tissue culture documentary videos which were very valid for use in the learning process.